2020
DOI: 10.2147/cmar.s250171
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Targeting PIK3CG in Combination with Paclitaxel as a Potential Therapeutic Regimen in Claudin-Low Breast Cancer</p>

Abstract: Purpose: Molecular targeting is a powerful approach for aggressive claudin-low breast cancer (CLBC). Overexpression of PI3K catalytic subunit gamma (PIK3CG) in human CLBC is offering a promising opportunity for targeted therapies. We utilized a specific inhibitor of PIK3CG combined with paclitaxel (PTX) to treat CLBC cells in vitro and in vivo. Patients and Methods: The tumor cells growth and apoptosis in vitro were analyzed by CCK8, plate clone formation assay, tumorsphere assay, Hoechst staining and flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…31 PIK3CG is an upregulated gene and a subunit of PI3K, which is closely related to various tumors. 32 AKT1 is a downregulated gene and is highly expressed in tumor tissues. It can participate in tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…31 PIK3CG is an upregulated gene and a subunit of PI3K, which is closely related to various tumors. 32 AKT1 is a downregulated gene and is highly expressed in tumor tissues. It can participate in tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that PIK3CG is also a potential target for the treatment of few malignant tumors such as acute lymphoblastic leukemia, medulloblastoma and Kaposi sarcoma. 45 …”
Section: Resultsmentioning
confidence: 99%
“…It is reported that PIK3CG is also a potential target for the treatment of few malignant tumors such as acute lymphoblastic leukemia, medulloblastoma and Kaposi sarcoma. 45 The most signicant molecular functions were enzyme binding, RNA polymerase II transcription factor activity and transcription factor binding. Meanwhile, the most involved cellular components were cytosol, endoplasmic reticulum membrane and nucleus (Fig.…”
Section: Gene Ontology (Go) Enrichment Analysis For Targetsmentioning
confidence: 99%
“…For example, ribosomal protein S6 (RPS6) was associated with breast cancer by targeting miR-129-5p [36] and regulating PIK3CA [37]. Recent work suggested that PIK3CG was a targeted therapy for claudin-low breast cancer; we also found the quantitative target gene of the given drug [38]. The diagram shown in Figure 3 illustrates an aggregation of both negative and positive quality interactions presented in Table 2.…”
Section: Mtor Pathwaymentioning
confidence: 88%